A pilot study of the utility of a hospital-based school program for pediatric patients with cardiac diagnoses - Thibodaux, Lia K.; Orr, Ashley L.; Reisinger, Debra L.; Fodstad, Jill; Xu, Guang; Wikel, Kristin; Curtin, Michelle (Frontiers in Pediatrics, 2024)
Introduction: Pediatric patients with complex cardiac diagnoses have increased risk physical, cognitive, and developmental complications. Formalized school supports (i.e., individualized education programs [IEPs], Section 504 Accommodation Plans [Section 504 Plans]) that address these needs are necessary and Hospital-Based School Programs (HBSPs) have the potential to bolster acquisition. In this pilot study, we look at the impact of one HBSP. Methods: Retrospective demographic and school support data for pediatric cardiac patients were analyzed. Results: Our sample included 29 pediatric cardiac patients spanning two academic years. These patients had 100 HBSP encounters, 82 inpatient and 12 outpatient, with 68.9% of patients having multiple encounters in a single year, and 44.8% of patients being seen in both years. The HBSP made recommendations for patients to receive IEPs (N = 8) and Section 504 Plans (N = 13). They also submitted requests for medical homebound (N = 27), obtaining releases of information (N = 39), submitting medical reports (N = 10), and completing certificates of incapacity (N = 7). Statistical analyses revealed no significant relationships with patients entering or receiving a recommendation for an IEP or Section 504 Plan across any of their encounters by the HBSP on the basis of sex, race/ethnicity, school level, or rates of encounters in this sample. Discussion: Similar to previous studies, these patients had high rates of IEPs/Section 504 Plans in place and continued to receive school recommendations by the HBSP. High use of the HBSP was seen in the total number of encounters and communications (i.e., submitting to the school of record requests for classroom placement changes via medical homebound). Working with the HBSP provided access to information, formal support recommendations, and communication between medical and school settings in the form of changes in school status.